A‐Site Cation Replacement of Hydrazinium Lead Iodide Perovskites by Borane Ammonium Ions: A DFT Calculation - Mohammad Tanvir Ahmed; Shariful Islam; Prof. Dr. Farid Ahmed (ChemistryOpen, 2024)
Abstract Organometallic perovskites have become one of the most common multifunctional materials in optoelectronic research fields. This research studies density functional theory calculation on orthorhombic hydrazinium lead iodide (N2H5PbI3) perovskite by replacing A‐site cation with a borane ammonium (BH2NH3+) ion. The perovskite showed a significant structural deformation and an orthorhombic to triclinic phase transition due to A‐site ion replacement. The N2H5PbI3 perovskite has a band gap of 1.64 eV, suitable for the solar cell absorber layer. The band gap has increased to 2.12 eV after complete A‐site ion replacement. All structures showed a high absorption coefficient over 104 cm−1 in the low wavelength region and an increase in refractive index from 2.5 to 2.75 due to ion replacement. All the structures showed high optical conductivity of 1015 s−1 order in the blue wavelength region. These new perovskite structures hold the potential to provide a revolution in optoelectronic research.